Enhancing Maritime Security In Indonesia: A Case Study Of Indonesian Coastguard Approach To People Smuggling In Strategic Ocean - Ola Oktavia; Jonni Mahroza; Lukman Yudho Prakoso; Tasdik, Tasdik; Sri Patmi; Rudi Sutanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
In the face of globalization and increasing maritime trade, the Maritime Security Agency of the Republic of Indonesia (Indonesian Coast GuardRI) plays an important role in safeguarding the country's waters, particularly the Makassar Strait, against the threat of people smuggling . This study evaluated Indonesian Coast Guard RI's strategy to combat people smuggling , focusing on personnel capacity building, interagency collaboration, and strict regulatory enforcement. This research uses normative legal research methods, using legislative, conceptual, and historical approaches. It belongs to the category of descriptive research, using secondary data consisting mainly of primary legal material (legislation) and secondary legal material in the form of textbooks and scientific journals on people smuggling. The analysis shows (1) indonesian maritime security agency by joint operations and interagency synergy, personnel capacity enhancement, security and safety patrol mandate (2) maritime routes poses through analysis of specific incidents, evaluation of countermeasures, utilization of technology and intelligenc, (3) evaluation of method and strategy effectiveness through training impact on personnel, interagency collaboration, implementation and regulatory compliance, (4) exploration of new technology potential through advanced surveillance system utilization, integration of artificial intelligence, data-driven approaches, (4) analysis of motivations and tactics through analysis of perpetrator motivations, analysis of smuggling and people smuggling  tactics. Conclusion of this research is that Indonesian Coast Guard  holistic approach, coupled with collaboration with relevant agencies, has positively impacted the reduction of people smuggling  incidence. Nevertheless, challenges remain, requiring further research to optimize strategies to more effectively ensure Indonesia's maritime security against the threat of people smuggling .